Percutaneous Transthoracic Lung Biopsy: Optimizing Yield and Mitigating Risk. Issue 5 (4th September 2021) - Azour, Lea; Liu, Shu; Washer, Sophie L.; Moore, William H.
Abstract: Percutaneous computed tomography–guided transthoracic lung biopsy is an effective and minimally invasive procedure to achieve tissue diagnosis. Radiologists are key in appropriate referral for further workup, with percutaneous computed tomography–guided transthoracic lung biopsy performed by both thoracic and general interventionalists. Percutaneous computed tomography–guided transthoracic lung biopsy is increasingly performed for both diagnostic and research purposes, including molecular analysis. Multiple patient, lesion, and technique-related variables influence diagnostic accuracy and complication rates. A comprehensive understanding of these factors aids in procedure planning and may serve to maximize diagnostic yield while minimizing complications, even in the most challenging scenarios.